2009
DOI: 10.1007/s00384-009-0846-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of pouch compliance measurement in the management of pouch dysfunction

Abstract: Measuring pouch compliance does not offer new information accounting for idiopathic pouch dysfunction and has little influence on the clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Their first article looked at the role of pouch compliance testing in differentiating patients with overt pouch disease from those with pouch dysfunction, testing 75 and 66 patients, respectively. 7 The main symptoms of the pouch dysfunction group were high defecatory frequency, incontinence, and evacuation difficulties (incidentally, a finding similar to that of our series of patients with ineffective pouch emptying). 21 The study found no difference in pouch compliance between different types of pouches (J versus S versus W), nor did compliance differ between the group with pouch dysfunction and those with overt pathology.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Their first article looked at the role of pouch compliance testing in differentiating patients with overt pouch disease from those with pouch dysfunction, testing 75 and 66 patients, respectively. 7 The main symptoms of the pouch dysfunction group were high defecatory frequency, incontinence, and evacuation difficulties (incidentally, a finding similar to that of our series of patients with ineffective pouch emptying). 21 The study found no difference in pouch compliance between different types of pouches (J versus S versus W), nor did compliance differ between the group with pouch dysfunction and those with overt pathology.…”
Section: Methodssupporting
confidence: 83%
“…Navaneethan and Shen 20 focused their discussion on pouchitis and pouch dysfunction almost exclusively on pouchitis, whereas the team from St. Mark's Hospital were much more on target in 3 articles from 2010, 2016, and 2018. [7][8][9] They appropriately defined pouch dysfunction as patients with symptoms in whom an extensive evaluation failed to show any overt disease. Their first article looked at the role of pouch compliance testing in differentiating patients with overt pouch disease from those with pouch dysfunction, testing 75 and 66 patients, respectively.…”
Section: S40mentioning
confidence: 99%
“…Small‐ or large‐volume pouches and those with afferent limb abnormalities were uncommon (Table ), and for this reason the present study did not attempt to correlate symptoms of evacuation difficulty with the radiological findings in such cases. Previous work involving the measurement of pouch compliance showed that functional symptoms were not related to the capacitance or volume of the pouch, indicating that its physical features may have little to do with some of the functional symptoms . Instilling contrast into the pouch may straighten the small bowel and therefore not reveal obstruction caused by a flap‐valve mechanism.…”
Section: Discussionmentioning
confidence: 98%